IGYIP Bulletin - IGLYO Bulletin - Speak Out. (Oslo vanaf (1988) : Amsterdam : International Lesbian and Gay Youth Organisation, 1986)
Fonds Suzan Daniel (FSD)
Periodiciteit : driemaandelijks
Redactie : PO Box 1305 Vika, 0112 Oslo 1 ; vanaf (1988) IGLYO c/o LHJO, PO box 542, 1000 AM Amsterdam
Vanaf (1986) 1 : IGLYO Bulletin ; vanaf (1986) 2 : Speak Out
Engels
Periodiek
Keywords: Holebibladen